Pseudomembranous Colitis – a review - Carvalho, Aline Vasconcelos; Medeiros-Júnior, Arnaldo Costa de; Chaves, Bárbara Monitchelly Fernandes; Xavier, Clara Rafael Silva; Rêgo, Amália Cíntia Meneses do; Araújo-Filho, Irami; Medeiros, Aldo da Cunha (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2014)
Pseudomembranous colitis is a disease caused by Clostridium difficile that predominantly affects the lower gastrointestinal tract. Its main risk factors are antibiotic use, advanced age and hospitalization. We used the keywords Pseudomembranous colitis, Clostridium difficile, Antibiotics, Pseudomembranous, Fulminant colitis, and the search was performed in PubMed, Virtual Health Library-Brazil, Embase and Scopus. Pathogenesis is not fully understood. The most frequent clinical presentation occurs with typical symptoms. Laboratory identification of C. difficile toxin in the stool sample and / or viewing pseudomembranes in endoscopy are essential for a definitive diagnosis. The initial drug treatment is available, however many complications can occur, and surgery may be performed for the most severe cases. The current available technologies are not yet able to resolve all cases. So many other challenges must be overcome regarding the treatment and its pathogenesis, especially in refractory and recurrent disease.